Using implementation mapping for the adoption and implementation of Target:BP in community health centers - Valerio-Shewmaker, Melissa A.; Heredia, Natalia I.; Pulicken, Catherine; Mathews, Patenne D.; Chenier, Roshanda; Swoboda, Tracy L.; Garza, Ella R.; Velasco-Huerta, Fernanda; Fernandez, Maria E. (Frontiers in Public Health, 2022)
Background Despite the availability of multilevel evidence-based interventions for blood pressure management, poor hypertension control is common among community health center patient populations across the state of Texas and the United States. Target:BPTM is a national initiative from the American Heart Association and the American Medical Association to assist healthcare organizations and care teams in improving blood pressure control rates using evidence-based approaches and recognition of organizations who have successfully integrated the program in their practice. Using the Implementation Mapping approach, we identified determinants of Target:BPTM adoption and use and developed implementation strategies to improve program uptake and implementation in Community Health Centers in Texas. Methods We used Implementation Mapping (IM) to identify barriers and facilitators influencing the adoption and implementation of the Target:BPTM program and develop strategies to increase program adoption and use. We recruited four clinics across four counties in Texas and assessed barriers and facilitators at the organizational level, including electronic health records and data use. We used this data to inform clinic-specific implementation strategies based on the organization capacity and priorities feedback. We developed an implementation plan and timeline designed to improve the implementation and maintenance of Target:BPTM. Results As part of the needs and capacity assessment, we collected data through interviews with CHC staff, examining gaps in needs and services (e.g., what do clinics need to implement Target:BPTM?), and assets to leverage. We worked with Community Health Centers to a) identify individuals who would be involved in the adoption, implementation, and maintenance of Target:BPTM, b) describe adoption and implementation actions, and c) identify barriers and facilitators influencing adoption and implementation. Together with partners from Community Health Center, we used the IM approach to identify and develop program goals, identify methods and strategies to address barriers, and create an implementation plan. Our strategies included monthly or biweekly meetings to provide technical support, reviewing program goals and timeline to ensure program implementation, progress toward reaching goals, and address quality improvement needs at each clinic site. We developed a Target:BPTM implementation protocol for each clinic based on the needs and capacity assessment, identification of technology use and capacity, and gap analysis. We reviewed Target:BPTM program strategies and self-measured blood pressure protocols tailored to the clinic patient population. We developed a collaborative plan, reviewed funding and capacity for implementation, and provided continuous quality improvement guidance. Ongoing process and impact evaluations using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework are underway. Discussion This paper provides an example of using Implementation Mapping to develop strategies to increase the adoption and implementation of evidence-based cardiovascular risk reduction interventions in Community Health Centers. The use of implementation strategies can increase the use of Target:BPTM in Community Health Centers and improve hypertension control.